2020
DOI: 10.1111/php.13300
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy and Immune Checkpoint Blockade

Abstract: Immune checkpoints including PD‐1 and CTLA‐4 help to regulate the intensity and timeframe of the immune response. Since they become upregulated in cancer and prevent sufficient antitumor immunity, monoclonal antibodies against these checkpoints have shown clinical promise for a range of cancers. Multimodal treatment plans combining immune checkpoint inhibitors with other therapies, including photodynamic therapy (PDT), may help to expand treatment efficacy and minimize side effects. PDT's cytotoxic effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Antitumor physical therapy can cause the death of tumor cells and the release of tumor antigens, which up-regulates the expression of MHC-I complex on tumor cells and promotes the maturation of antigen-presenting cells. Subsequently, the activation and proliferation of effector T cells are initiated by antigen-presenting cells, thus exerting anti-tumor immune response ( Brodin, Guha & Tomé, 2015 ; Chen et al, 2020 ; Cramer et al, 2020 ; Eckert et al, 2019 ). However, studies have shown that radiotherapy and PDT can up-regulate the expression of PDL1 in tumor, weakening the anti-tumor immune response ( Deng et al, 2014 ; O’Shaughnessy et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Antitumor physical therapy can cause the death of tumor cells and the release of tumor antigens, which up-regulates the expression of MHC-I complex on tumor cells and promotes the maturation of antigen-presenting cells. Subsequently, the activation and proliferation of effector T cells are initiated by antigen-presenting cells, thus exerting anti-tumor immune response ( Brodin, Guha & Tomé, 2015 ; Chen et al, 2020 ; Cramer et al, 2020 ; Eckert et al, 2019 ). However, studies have shown that radiotherapy and PDT can up-regulate the expression of PDL1 in tumor, weakening the anti-tumor immune response ( Deng et al, 2014 ; O’Shaughnessy et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Various studies have profoundly demonstrated that PDT can cause immunogenic cell death (ICD) to release damage-associated molecules and consequently improve the immunogenicity of tumors 169 . Moreover, the combination of PDT with checkpoint-blockade immunotherapy can better eliminate primary tumors, inhibit metastasis, and prevent recurrence 179 . For example, Xu et al 180 synthesized UCNPs to simultaneously load Ce6 and imiquimod (R837, a Toll-like-receptor-7 agonist) for immuno-PDT.…”
Section: Pdt-involved Multimodal Therapiesmentioning
confidence: 99%
“…These factors could serve to promote synergy between PDT and immune checkpoint blockade. 76 Currently, the main ICB therapy using indoleamine 2,3-dioxygenase (IDO), anti-programmed death-ligand 1 (αPD-L1), anti-programmed death 1 (αPD-1), and anticytotoxic T lymphocyte-associated antigen 4 (αCTLA-4) antibodies have exhibited great capability in clinics. Treated antibodies can block IDO, 77 CTLA-4, 78 or PD-1, 79 and dramatically lengthen the overall survival of various cancer patients.…”
Section: Strategies Of Relieving Immunoregulatory Suppressionmentioning
confidence: 99%